The extraordinary deaths of Mrs. Kip - Brunsvold, Sara, 1979- (Revell, a division of Baker Publishing Group, 2022)
"Frustrated reporter Aidyn Kelley begrudgingly agrees to help a hospice patient prepare her obituary. But old Clara Kip has some incredible stories-and some surprises up her sleeve-that promise to make this seemingly throwaway assignment a life-changing one"--